Risk Analysis of Surabaya – Bojonegoro Highway Improvement Project Based on Fuzzy Logic - Nova Nevila Rodhi (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
Infrastructure development is one of the efforts to improve the welfare of the community, but in its implementation, road construction projects have risks that can have an impact on the project as well as on the external side of the project. This research is a case study on the road widening project of Bojonegoro – Surabaya KM 107. The purpose of this research is to analyze the risks in the project using fuzzy logic. Based on the results of the analysis, it can be concluded that the Bojonegoro - Surabaya highway widening project has 10 risk factors, namely noise, air pollution, heavy equipment vibration, traffic accidents, congestion, reduced parking space, increased fuel consumption of road users, decreased income of people in surrounding locations, conflict between road users, covid 19. The results of the analysis using a risk matrix, all risk factors are at a moderate level, but the results of the analysis using fuzzy, there are 2 risks that are at a high level, namely traffic congestion and a decrease in people's income in surrounding locations.